The effectiveness of mixtures of tetracycline, acid and detergent, and mixtures of chlorhexidine and ethylenediaminetetraacetic acid in preventing the growth of Enterococcus faecalis: An Ex vivo study - Tien Suwartini; Elfira Anggraini; Meiny Faudah Amin; Boedi Oetomo Roeslan (Wolters Kluwer Medknow Publications, 2020)
Background: Sodium hypochlorite (5.25% NaOCl) is the gold standard among irrigation solutions, but it is toxic to periapical tissue, decreases the micromechanical characteristics of dentin, has no effect on smear layer removal, and may not completely eradicate biofilms. Therefore, many new irrigation solutions, such as mixtures of tetracycline, citric acid, and detergent (MTAD) and a mixture of chlorhexidine (CHX) and ethylenediaminetetraacetic acid (EDTA) have been introduced as the alternatives to NaOCl. Objectives: The objectives of this study are to analyze the differences in the effects of MTAD and mixtures of CHX and EDTA on the growth of Enterococcus faecalis ex vivo.Methods: This study used 28 lower premolars, divided into seven groups. Group I received MTAD. Group II received MTAD with CHX. Group III received a mixture of CHX and EDTA. Group IV received a 2% CHX solution. Group V received 17% EDTA. Group VI received a 5.25% NaOCl solution, which served as the positive control, and Group VII received sterile distilled water, which was the negative control. The effectiveness of various irrigation solutions in preventing the growth of E. faecalis was measured by the zone of growth inhibition and colony counts. Results: A one-way analysis of variance revealed a significant difference among the tested irrigation solutions, both in terms of zone inhibition of E. faecalis and E. faecalis colonies counting (P < 0.05). Conclusion: There was a different antibacterial effect between MTAD and the mixture of CHX and EDTA. MTAD were more effective as irrigation solution compared to the mixture of CHX and EDTA. However, as irrigation solutions, both were less effective than 5.25% NaOCl.